Influence of the Isothermal Transformation Temperature on the Structure and Properties of Low-Carbon Steel - Vakulenko, Ihor O.; Plitchenko, Serhii O.; Asgarov, Khangardash; Lytvynov, Bohdan V.; Orak, Abdulkadir; Umur, Hakan (Український державний університет науки і технологій, Дніпро, 2024)
ENG: Purpose. The study is aimed at evaluating the effect of the isothermal transformation temperature on the structure and properties of low-carbon steel. Methodology. The material for the study was a 3 mm diameter wire made of mild steel with the following chemical composition: 0.21% C, 0.47% Mn, 1.2% Si, 0.1% Cr, 0.03% S, 0.012% P. The 0.3 m long wire samples were subjected to austenitizing at 920 °C for 8...9 min, after which they were held iso-thermally for 11 min at temperatures of 650...200 °C, followed by cooling in air. The strength, plastic properties, and strain hardening coefficient were determined from the analysis of tensile curves. Findings. It was found that a decrease in the temperature of isothermal transformation, starting from 450...400 °C, increases the amount of Widmannstätten ferrite due to the disappearance of polyhedral ferrite grains. At the same time, the number of areas with locally located dispersed cementite particles similar to pearlite colonies increases, and bainite crystals appear. Against the background of a sharp decrease in the strain hardening coefficient in the range of 450...400 °C, the ability of the bainite phase to undergo plastic deformation should be considered one of the reasons for the delay in den-sity reduction. Originality. The effect of steel hardening with a decrease in the pearlite transformation temperature is based on the grinding of ferrite grains, an increase in the amount of Widmannstätten ferrite, and the dispersion of pearlite colonies. The strengthening effect of steel with a bainite structure is based on an increase in the degree of supersaturation of the solid solution with carbon atoms and dispersion hardening by particles of the carbide phase. Practical value. The optimal structural state of steel intended for the manufacture of such critical elements as a sup-port beam, railroad car bogie, etc. is a mixture of phase components with different dispersion and morphology, and their quantitative ratio is determined by the operating conditions of a particular product.

UKR: Мета. Дослідження спрямовано на оцінку впливу температури ізотермічного перетворення на структуру та властивості низьковуглецевої сталі. Методика. Матеріалом для дослідження був дріт діаметром 3 мм, виготовлений із низьковуглецевої сталі з таким хімічним складом: 0,21 % C, 0,47 % Mn, 1,2 % Si, 0,1 % Cr, 0,03 % S, 0,012 % P. Зразки дроту довжиною 0,3 м піддавали аустенізації за температури 920 °С протягом 8…9 хв, після чого виконували ізотермічну витримку протягом 11 хв за температур 650…200 °C з подальшим охолодженням на повітрі. З аналізу кривих розтягу визначали міцність, пластичні властивості та коефіцієнт деформаційного зміцнення. Результати. Установлено, що зниження температури ізотермічного перетворення, починаючи з 450…400 °С, збільшує кількість фериту Відманштеттена за рахунок зникнення поліедричних феритових зерен. При цьому збільшується кількість ділянок із локально розташованими дисперсними частинками цементиту, схожими на колонії перліту, та з’являються кристали бейніту. На фоні різкого зниження коефіцієнта деформаційного зміцнення в діапазоні 450…400 °C однією з причин затримки зниження щільності слід вважати здатність бейнітної фази до пластичної деформації. Наукова новизна. Ефект зміцнення сталі зі зниженням температури перетворення перліту заснований на подрібненні зерен фериту, збільшенні кількості фериту Відманштеттена та дисперсії колоній перліту. Зміцнювальний ефект сталі зі структурою бейніту ґрунтується на підвищенні ступеня перенасичення твердого розчину атомами вуглецю та дисперсійного зміцнення частинками карбідної фази. Практична значимість. Оптимальний структурний стан сталі, призначеної для виготовлення таких відповідальних елементів, як опорна балка, візок вагона та ін., становить суміш фазових складових із різною дисперсністю та морфологією, а їх кількісне співвідношення визначають за умовами експлуатації конкретного виробу.
Вплив температури ізотермічного перетворення на структуру і властивості низьковуглецевої сталі
I. Vakulenko: ORCID 0000-0002-7353-1916; S. Plitchenko: ORCID 0000-0002-0613-2544; K. Asgarov: ORCID 0000-0003-4771-3406; B. Lytvynov: ORCID 0009-0008-1859-7470; A. Orak: ORCID 0000-0001-6611-4535; H. Umur: ORCID 0000-0003-4887-8093
Keywords: low-carbon steel; austenite; ferrite; temperature; isothermal transformation; dislocation; recrystallization; yield strength; низьковуглецева сталь; аустеніт; ферит; температура; ізотермічне перетворення; дислокація; рекристалізація; межа плинності; КПММ; TECHNOLOGY; TECHNOLOGY::Materials science